REFLEXÃO E DIÁLOGO SOBRE SUSTENTABILIDADE NO ENSINO BÁSICO E SUPERIOR: REFLECTION AND DIALOGUE ON SUSTAINABILITY IN PRIMARY AND FURTHER EDUCATION (Revista Contexto & Educação, 2021)
This study aimed to promote dialogue and reflection on sustainability based on previous knowledge of students in primary and further education at the Federal Institute of Paraná Campus Umuarama. It is an action research initiated with a diagnosis, composed of eight questions, applied to a sample of 36 students, forming three focus groups: 1) Ten high school students (primary education); 2) Twenty-one undergraduate students (further or college education); 3) Five students of the Masters in Sustainability (further education Stricto sensu Based on this diagnosis, an interactive lecture was organized to provoke reflection and dialogue on sustainability with the three groups gathered. It was observed that further education students, especially master's students, had greater knowledge on the subject. In addition, the interaction between students of different levels of education was beneficial, since the controversies and consensuses related to sustainability could be discussed between the actors of the study and the literature.